2011
DOI: 10.1002/ange.201102909
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control of One‐Pot Trans‐Splicing Reactions by Using a Wild‐Type and Designed Split Intein

Abstract: Keywords ion pairs; protein design; protein-protein interactions; semisynthesisCoulombic forces play an important role in facilitating protein-protein interactions. It has been demonstrated that a strong electrostatic potential between two interacting proteins correlates with a fast rate of association and a strong binding affinity. [1] Indeed, this principle has been exploited to enhance the binding properties of engineered protein interfaces. [2] Nonetheless, little research has focused on utilizing intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(29 reference statements)
0
10
0
1
Order By: Relevance
“…This problem has been alleviated in part by salt-inducible split inteins derived from a salt-inducible intein from extreme halophilic archaea, but yet requiring salt-induction for transsplicing 40 . Having more than two robust split inteins which are not cross-active (orthogonal) could widen the applications of PTS because two orthogonal split inteins enable us to perform three-fragment ligation efficiently 20,21,22,23 . Naturally split DnaE inteins such as NpuDnaE intein, however, are cross-active to other naturally occurring split DnaE inteins, despite its robust splicing activity and high tolerance of variations at the splice junctions 29,32,41 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This problem has been alleviated in part by salt-inducible split inteins derived from a salt-inducible intein from extreme halophilic archaea, but yet requiring salt-induction for transsplicing 40 . Having more than two robust split inteins which are not cross-active (orthogonal) could widen the applications of PTS because two orthogonal split inteins enable us to perform three-fragment ligation efficiently 20,21,22,23 . Naturally split DnaE inteins such as NpuDnaE intein, however, are cross-active to other naturally occurring split DnaE inteins, despite its robust splicing activity and high tolerance of variations at the splice junctions 29,32,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been suggested that local charge distributions between naturally split intein halves are important for their association 18,23,29 . We observed extensive charge-charge interactions in the crystal structure of the gp41-1 intein, as observed among other naturally split inteins 29 .…”
Section: The Charge Network In the Gp41-1 Inteinmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The NpuN and NpuC intein fragments were obtained from vectors provided by Tom W. Muir (Princeton University). 28 DNA oligonucleotides were obtained from Integrated DNA Technologies (Coralville, IA).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%